High Expression Levels of SIGLEC9 Indicate Poor Outcomes of Glioma and Correlate With Immune Cell Infiltration - Xu, Heng; Feng, Yanyan; Kong, Weijia; Wang, Hesong; Feng, Yuyin; Zhen, Jianhua; Tian, Lichun; Yuan, Kai (Frontiers in Oncology, 2022)
Objective: To investigate the diagnose value and underlying mechanisms of Siglec9 in gliomas. Patients and methods: TCGA and CGGA databases were used to analyze the association of Siglec9 expression levels with tumor stages and survival probability. Immunohistochemical staining of Siglec9 and survival analysis were performed in 177 glioma patients. Furthermore, related mechanisms were discovered about Siglec9 in glioma tumorigenesis. Results: TCGA and CGGA databases indicated that patients with high Siglec9 expression manifested significantly shorter survival probability than those with low Siglec9 expression. Siglec9 was significantly up-regulated in malignant pathological types such as grade III, grade IV, mesenchymal subtype, IDH wide type gliomas. Immunohistochemical staining of tissue sections from 177 glioma patients showed that Siglec9 high expression patients manifested significantly shorter survival probability than those Siglec9 low expression patients with age≧60, grade IV, GBM, ATRX loss, without radiotherapy or chemotherapy. Furthermore, Siglec9 expression level was positively correlated with MDSC infiltration and neutrophil activation. Siglec9 expression was also positively correlated with that of major immune checkpoints such as PDCD1, CTLA4, LAG3, and TIGIT. Conclusion: These findings suggested that Siglec9 is a diagnose marker of poor outcome in glioma and might serve as a potential the immunotherapy target of for glioma patients in the future.